Bush's 674 billion plan: Stimulus for re-election or building block for radical tax reform? - Jens van Scherpenberg (Stiftung Wissenschaft und Politik (SWP), 2003)
With the presentation of his 'Growth and Jobs Plan' on 7 January 2003, George W. Bush demonstrated his determination to avoid the fate of his father, whose neglect of the economy led to the failure of his 1992 presidential re-election bid. At the same time, however, Bush seeks to dramatically reduce the economic role played by the state; if he succeeds, he will stand as the man who completed the mission initiated by Ronald Reagan. Rather than substituting public demand for insufficient private demand in a Keynesian fashion, Bush seeks above all to provide far-reaching tax relief on private capital investments. Such a process of fundamental tax reform, which would presumably reach its climax during a second Bush administration, would give the U.S. international status as a low-tax country, thereby allowing it to attract the massive influx of private capital necessary for financing its ever-increasing current account deficit. Whether or not this succeeds in stimulating the U.S. economy, Bush's plan will heighten the reform pressure on Germany and other industrial nations experiencing sluggish economic growth. (SWP Comments / SWP)
Keywords: 320